Effect of Biochar on Peat Soil Fertility and NPK Uptake by Corn - Eni Maftu'ah; Dedi Nursyamsi (AGRIVITA, Journal of Agricultural Science, 2019)
This study aimed to investigate the biochar effect on peat soil fertility and uptake of nitrogen, phosphor, and potassium by corn plants. The experiment was conducted at a greenhouse in the Indonesian Swampland Agriculture Research Institute (ISARI), Banjarbaru, South Kalimantan, from June to September 2014. The peat soil sample was collected from the village of Kalampangan, Palangkaraya, Central Kalimantan. The treatment consisted of four types of biochar, namely coconut shell, palm midrib, Galam stem (Melaleuca leucadendron), rice husk and five rates of biochar i.e. 0, 2, 4, 8 and 16 t ha-1. Biochar was analyzed in total C, P, K, Ca, Mg, Fe, Si, ash content, pH and CEC, also initial soil sample was analyzed  pH, EC, organic C, total N, P, available P, exchangeable K, Ca, Mg, H, Cu, Zn, and total acidity were measured. The application of biochar changed peat soil properties including pH, available P, exchangeable K, nutrient uptake and the dry weight (i.e root and shoot). The type of biochar significantly affect the exchangeable K in peat soil and nutrient uptake. The highest exchangeable K and NPK uptake by corn showed by the coconut shell biochar at dose 4 t/ha.